Adopting Open-Source SD-WAN: A Comprehensive Analysis of Performance, Cost, and Security Benefits Over Traditional WAN Architectures - V. Arogundade, Segun; Sattar, Mian Usman; Wazir Khan, Hamza (EAI Endorsed Transactions on Scalable Information Systems, 2025)
Many enterprises are using cloud computing innovation and remote services to the maximum. Working from home is becoming the norm. Favored legacy Wide Area Networks (WANs) are not up to the tasks, as they are suffering due to lack of scalability with their traditional non-virtualized form as it still requires a lot of physical components. Update and maintenance of fickle hardware costs a lot. There is a need for more flexible and scalable networking solutions. Many enterprise solutions offer proprietary form of SD-WANs (Software-Defined Wide Area Networks), but they are costly and inflexible, which means they are not practical for all applications. This paper proposes an Open-source SD-WAN with OpenDaylight platform as core that we have tested in a simulated environment along with Mininet and Oracle Virtual Box to study various scenarios. Test results show that it provides a 35% increase in throughput, decreases 40% in latency, and reduces packet loss by 50%, compared to traditional WANs. Additionally with Open-Source nature, it has a 20% lower operational coupled with the problem mitigation factors listed above, which makes it a more potential solution for the current woes of businesses.